Assessment of the atrial electromechanical properties of patients with human immunodeficiency virus - Ahmet G. Ertem; Çağrı Yayla; Burak Açar; Sefa Ünal; Mehmet A. Erdol; Meliha Ç. Sonmezer; Esra Kaya Kiliç; Çiğdem Ataman Hatipoglu; Serkan Gokaslan; Habibe Kafes; Mehmet K. Akboga; Pelin Aladag; et al. (Elsevier, 2017)
The relationship between atrial fibrillation and human immunodeficiency virus (HIV) infection was evaluated. Electro-echocardiographic methods can be used to predict the development of atrial fibrillation (AF). In this study, we aimed to investigate the atrial electromechanical delay (AEMD) parameters of HIV (+) patients. Forty-two HIV (+) patients and 40 HIV (−) healthy volunteers were prospectively enrolled in this study. The electromechanical properties of the subjects' atria were evaluated with tissue Doppler imaging. The left-AEMD, right-AEMD and inter-AEMD were increased in the HIV (+) patients relative to the controls (p = 0.003, p < 0.001, and p < 0.001, respectively). The CD4 count was inversely correlated with the inter-AEMD (r = −0.428, p < 0.001). The CD4 count was an independent predictor of the inter-AEMD (β = 0.523, p = 0.007). Our study demonstrated that both the inter- and intra-atrial electromechanical delays were prolonged in the patients with HIV. This non-invasive and simple technique may provide significant contributions to the assessment of the risk of atrial arrhythmia in patients with HIV. Keywords: Atrial electromechanical delay, Echocardiography, Human immunodeficiency virus